Expression of Gender Inequalities in Wage Differences in the European Labor Market - Thidphaxay Souliya (Humán Innovációs Szemle)
According to universal laws guaranteeing the enforcement of human rights, every individual has the right to equal opportunities to thrive in life and the job market, regardless of gender, ethnicity, religion, national origin, political or other ideological commitments, age, or whether they have any disabilities (United Nations 1948).